Usefulness of High-Resolution 3D Multi-Sequences for Peripheral Facial Palsy: Differentiation Between Bell's Palsy and Ramsay Hunt Syndrome. Issue 10 (December 2017) - Kuya, Junko; Kuya, Keita; Shinohara, Yuki; Kunimoto, Yasuomi; Yazama, Hiroaki; Ogawa, Toshihide; Takeuchi, Hiromi
Abstract : Objective: To investigate the usefulness of magnetic resonance imaging (MRI) including three-dimensional (3D) sequences in the differentiation between Bell's palsy (BP) and Ramsay Hunt syndrome (RHS). Study Design: A prospective study. Setting: Tertiary care center. Patients: Twenty patients: 15 patients with BP and five patients with RHS. Intervention: Diagnostic. Main Outcome Measure: Clinical diagnosis (BP or RHS). Results: The presence of hyperintensity on 3D-fluid-attenuated inversion recovery sequence (3D-FLAIR) and enhancement on gadolinium-enhanced (CE)-3D-FLAIR and CE-3D-T1-weighted image (3D-T1WI) along the internal auditory canal (IAC) wall were significantly associated with RHS ( p  < 0.05). Hyperintensity in the inner ear was observed on pre- and postcontrast 3D-FLAIR, and enhancement of the cranial nerve (CN)-VIII was observed only on CE-3D-FLAIR. The presence of these findings also showed significant relationships with RHS ( p  < 0.05). Moreover, thickening of the CN-VII in the fundus of the IAC in 3D-constructive interference on steady state sequence (3D-CISS) also showed a significant association with RHS ( p  < 0.05). In contrast, the presence of hyperintensity of the CN-VII in the fundus of the IAC on 3D-FLAIR did not demonstrate a significant relationship ( p  = 0.95), and enhancement in this region was observed in all cases on CE-3D-FLAIR and gadolinium-enhanced-three-dimensional-T1-weighted gradient echo sequence (CE-3D-T1WI). Conclusions: 3D MRI sequences are useful for differentiating RHS from BP. In particular, the enhancement in the CN-VIII and/or along the IAC wall are valuable findings, and CE-3D-FLAIR is the most useful sequence to evaluate these findings. Thickening of the CN-VII on 3D-CISS is also an important finding.